The Consumer acceptance of catfish (Pangasius hypophthalmus) nugget by soaked with liquid smoke - Yandri Permana Saputra; Sukirno '; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intended to determaine the effect of using liquid smoke catfish onthe nugget towards consumer acceptance measured by organoleptic value andchemical value analysis. The method used in this study was experimental, the designwas completely random design with three treatment i.e K0 ( 500g fresh fish meat), K1(400g soaked catfish meat by liquid smoked), K2 (300g soaked catfish meat by liquidsmoked). The K2 treatment (300g soaked catfish meat by liquid smoked)was the besttreatments refers to organoleptic value (form, flavor, aroma, and texture),alsochemical value with the form criteria was browning yellow, the flavor criteria wassoftening smoke,the texture criteria is not too hard and the aroma criteria was not toosharp smoke smell with 54,46% water amount, 18,13% protein amount and the pHvalue 5,81.Keyword:liquid smoke, catfish, Consumer acceptance